Pediatric palliative care and end-of-life: a systematic review of economic health analyses - Denise Swei Lo; Noely Hein; Jaqueline Vilela Bulgareli (Sociedade de Pediatria de São Paulo, 2022)
Abstract Objective: To perform a systematic review of the health economic evidence on the care of children and adolescents with complex clinical conditions, comparing groups included and not included (control group) in palliative care at the end of life. Data source: The seven databases searched were PubMed, Embase, Web of Science, Cochrane Library, Virtual Health Library-Latin American and Caribbean Health Sciences Literature (VHL-LILACS), EBSCOhost, and Paediatric Economic Database Evaluation, following recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Statement, from January 1979 to November 2020. The review included studies of patients under 18 years of age with complex clinical conditions that compared a palliative care group with a control group. The economic outcomes analyzed were length and place of stay at the end of life (home, hospice, ward, intensive care unit, emergency room), diagnostic and therapeutic procedures performed, and health-related costs. The exclusion criteria were: studies without a matched control group, conference/congress abstracts, letters to the editor, editorials, comments, qualitative studies, narrative reviews, studies with ten or fewer participants in each group, articles published in languages other than English, Portuguese, or Spanish. Data synthesis: Out of the 518 articles identified, 4 met the inclusion criteria. We found evidence of direct economic benefits, such as reduced health costs, indirect savings, and protection of patients from undergoing invasive procedures, surgeries, and costly therapies, which cause greater suffering at the end of life. Therefore, participating in a palliative care program saved financial and technological resources, besides increasing the frequency of deaths at home and improving the quality of life. Conclusions: Public and private policies to promote palliative care represent better efficiency when allocating available health care resources.